2021
DOI: 10.1007/s00784-021-03917-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of COVID-19 pandemic on paediatric dental attendance

Abstract: Objectives This retrospective study aimed to evaluate the effect of COVID-19 pandemic on dental attendance and emergency/ non-emergency visits of children during the outbreak, compared to the same period of 2019. Materials and methods Patients who visited the paediatric department clinic during the observed period were included in this study. The patient's demographic data, purpose of visit, and treatment type were evaluated retrospectively from patient examination records. The Pearson chi-square and t-tests w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
28
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 14 publications
8
28
0
2
Order By: Relevance
“…Karacin C et al 19 has reported 31.1% patients approaching pediatric dentist due to pain as in our study. A study by Ustun N et al 12 showed that most of the children exhibited dental pain from pulpal inflammation, abscess and swelling in this pandemic. In a study by Fux-Noy A et al 20 it was seen that most of the pediatric patients arrived with emergency such as dental pain, swelling, or dental trauma during the lockdown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karacin C et al 19 has reported 31.1% patients approaching pediatric dentist due to pain as in our study. A study by Ustun N et al 12 showed that most of the children exhibited dental pain from pulpal inflammation, abscess and swelling in this pandemic. In a study by Fux-Noy A et al 20 it was seen that most of the pediatric patients arrived with emergency such as dental pain, swelling, or dental trauma during the lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…Study by Humagain M et al 11 showed that only 10% of the Nepalese dentists were doing dental treatments especially emergency and urgent cases during the lockdown. Ustun N et al 12 observed that there was a decrease in pediatric dental attendance by half during the pandemic period. Similar to our findings, Guo H et al 13 and Tobias G et al 14 also reported decrease in the number of patients visiting the dental emergency clinic in Beijing and Israel respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in our study, the most common emergency situations were reported as severe pain caused by pulpal inflammation (94%), abscesses or bacterial infection causing localized pain and extraoral swelling (86.5%), luxations/dental avulsions (41%), dental fractures causing pain, or soft tissue injuries caused by trauma (35.5%). Ilyas et al [61] reported irreversible pulpitis, Moheb et al [13] reported severe pain, infection and trauma, Üstün et al [62] reported severe dental pain because of pulpal inflammation and swelling, Faccini et al [58] reported toothache (71.4%), broken restorations (40.4%) and dental trauma (37.3%), Alsaleh et al [14] reported abscesses (51.8%) and cellulitis (44.6%) in Jordan and abscesses (44.6%) and pulpitis (35.5%) in India, Izzetti et al [16] reported pulpitis, prosthesis de-cementation and abscesses, and Sinjari et al [55] reported severe dental pain, swelling and dental trauma as the most common emergency situations managed. Thus, the findings of this study were found to be in accordance with those others [13,14,16,55,58,61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Ilyas et al [61] reported irreversible pulpitis, Moheb et al [13] reported severe pain, infection and trauma, Üstün et al [62] reported severe dental pain because of pulpal inflammation and swelling, Faccini et al [58] reported toothache (71.4%), broken restorations (40.4%) and dental trauma (37.3%), Alsaleh et al [14] reported abscesses (51.8%) and cellulitis (44.6%) in Jordan and abscesses (44.6%) and pulpitis (35.5%) in India, Izzetti et al [16] reported pulpitis, prosthesis de-cementation and abscesses, and Sinjari et al [55] reported severe dental pain, swelling and dental trauma as the most common emergency situations managed. Thus, the findings of this study were found to be in accordance with those others [13,14,16,55,58,61,62]. However, differently from our findings, Limbu et al [63] reported exfoliating mobility (23.3%), acute pulpitis (5.8%) and dental abscesses (22.1%), and Martinho and Griffin [18] reported trauma (82.1%) followed by swelling (81.9%) and pain (76.1%) as dental emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…Ülkemizde, Üstün ve ark. tarafından yapılan bir çalışmada, acil olmayan rutin diş hekimliği hizmetleri kapsamında özellikle koruyucu diş hekimliği uygulamalarında (fissür örtücü, flor tedavisi) ciddi oranda düşme olduğu, diş kliniğine başvuru nedeni olarak acil diş hekimliği şikayetlerinin ön plana çıktığı görülmektedir (21). Pulpitise bağlı diş ağrısı, apse ve şişlik en sık bildirilen acil diş hekimliği şikâyetler arasında yer almaktadır.…”
Section: Covid-19 Ve Ağız Sağlığı Hizmetleriunclassified